Imaging Recommendations for Diagnosis, Staging, and Management of Lung Cancer - Irodi, Aparna; Bhalla, Ashu Seith; Robinson Vimala, Leena; Yadav, Taruna; Adithan, Subathra; Bhujade, Harish; Sanghavi, Parang; Kale, Alok; Garg, Mandeep; Mahajan, Abhishek; Jaykar David Livingstone, Yvette Kirubha; Das, Sudha Kiran; H., Geethi M.; Sasidharan, Balukrishna; Thangakunam, Balamugesh; Pavamani, Simon; Isiah, Rajesh; Joel, Anjana; Bhat, Tameem Ahmad (Indian Journal of Medical and Paediatric Oncology, 2023)
Globally and in India, lung cancer is one of the leading malignancies in terms of incidence and mortality. Smoking and environmental pollution are the common risk factors for developing lung cancer. Traditionally, lung cancer is divided into small cell and nonsmall cell types, with nonsmall cell carcinomas including squamous cell carcinoma, adenocarcinoma, and large cell carcinoma.In this review article, we describe the imaging recommendations and findings in the diagnosis, staging, and management of lung cancer, including the imaging of treatment-related complications.
Keywords: cancer; imaging; lung; recommendations